Relasi Sosial Antara Pondok Pesantren Husnul Khotimah dengan Masyarakat Desa Maniskidul Kecamatan Jalaksana Kabupaten Kuningan - M. Iqbal Jabaludin; Syaiful Azmi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The Islamic boarding school is an institution that still exists now. Of course, it is not easy to maintain an Islamic boarding school as the times develop. The existence of pesantren is also threatened by a decrease in public trust caused by various cases by individuals who stigmatize negatively against pesantren which has an impact on decreasing the positive value for pesantren. This study aims to find out what and how the community contributes in maintaining Islamic boarding schools. This type of research is qualitative research using descriptive methods using a socio-religious approach. The research instruments are observation, interviews, and documentation. The result is that the cooperation carried out between Husnul Khotimah Islamic Boarding School and the people of Maniskidul Village covers three aspects including economy, religion, and education.